Ingesting the future: Navigating the perils of Nano-liquid urea A case study & Review of Literature (Journal of Forensic Medicine & Toxicology, 2025)
This case study aims to present the first documented suicide attempt involving the ingestion of nano-liquid urea, a nano technology-based fertilizer recently introduced in Indian agriculture. This study examines the clinical aspects including  signs, symptoms, laboratory investigations, and treatment, while simultaneously exploring the underlying psychosocial  aspects. By doing so, our goal is to illuminate the intersection between technological advancement, human vulnerability,  and the responsibilities that come with scientific innovation.
Keywords: Nano-liquid urea; suicide attempt; human vulnerability; uremic toxicity; mental health